E-Recruitment Sites: Management Graduates' Perception of an Online Application System (The Lumbini Journal of Business and Economics, 2022)
The study intends to examine various factors influencing management graduates’ perception of an online application system. A combination of stratified random, and convenience sampling methods was employed in this study. Through anexisting literature questionnaire and self-constructed questionnaire, 256 management graduates from nine campuses in the Rupandehi area provided data for the study on a five-point Likert scale. The research was conducted utilizing a descriptive and causal-comparative approach. Pearson Correlation Analysis and Simple regression equation estimated by the ordinary least square (OLS) method have been used. The empirical result finds that all of the independent variables investigated in the study were shown to have a significant positive relationship with the dependent variable. The outcome of the regression analysis indicates that fairness perceptions have the greatest influence on management graduates' evaluations of an online application system, followed by internet selection image and user-friendliness among the variables examined in this study. However, the outcome demonstrated that perceived efficiency and information provision have no significant effect.